2012
DOI: 10.1016/j.jiph.2012.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk of bloodborne pathogen exposure among Zambian healthcare workers

Abstract: The injury risks identified among Zambian workers are serious and are exacerbated by the high prevalence of bloodborne pathogens in the population. This suggests that there is a high risk of occupationally acquired bloodborne pathogen infection. The findings also highlight the need for a hepatitis B vaccination program focused on healthcare workers. The risks associated with bloodborne pathogens threaten to further diminish an already scarce resource in Zambia - trained healthcare workers. To decrease these ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
3
18
0
1
Order By: Relevance
“…These findings were consistent with studies by Orji et al and Fasunloro and Owotade in Nigeria [16,17]. Additionally, improper disposal of medical waste such as needles and other sharps has been found to cause injuries on HCWs which can also transmit blood borne diseases [10]. Lee in 2009 argued that the increase in acquisition of blood borne diseases by HCWs in developing countries is due to the high prevalence of HIV, HBV and HBC, hence making them more likely to acquire such blood borne diseases [15].…”
Section: Current Status Of Knowledge Transmission Of Blood Borne Pathsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings were consistent with studies by Orji et al and Fasunloro and Owotade in Nigeria [16,17]. Additionally, improper disposal of medical waste such as needles and other sharps has been found to cause injuries on HCWs which can also transmit blood borne diseases [10]. Lee in 2009 argued that the increase in acquisition of blood borne diseases by HCWs in developing countries is due to the high prevalence of HIV, HBV and HBC, hence making them more likely to acquire such blood borne diseases [15].…”
Section: Current Status Of Knowledge Transmission Of Blood Borne Pathsupporting
confidence: 91%
“…Post-exposure prophylaxis should be made available to HCWs who sustain needle stick injuries [43]. Health facilities should also have proper medical waste disposal systems to dispose of waste [10]. Additionally, Personal Protective Equipment (PPE) should be made accessible to HCWs with a written plan on how and when to use it [45].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 A recent survey of healthcare workers in Zambia found that 88% reported availability of PEP but only 8% were fully vaccinated against HBV. 32 To fully protect health care workers, HIV awareness is not enough. Further awareness and prevention of hepatitis, including access to HBV vaccination for healthcare workers, is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%